Hereditary hemorrhagic telangiectasia: an update on clinical manifestations and diagnostic measures = Hereditäre hämorrhagische Teleangiektasie : aktuelle Übersicht zu klinischen Krankheitsmerkmalen und diagnostischen Verfahren - Sadick, Haneen; Sadick, Maliha; Götte, Karl; Naim, Ramin; Riedel, Frank; Bran, Gregor M.; Hörmann, Karl (Wiener klinische Wochenschrift, 2006)
Hereditary hemorrhagic telangiectasia (HHT), also known as Rendu-Osler-Weber disease, is an autosomal dominant disorder of the fibrovascular tissue. It is characterized by the classic triad of (muco-)cutaneous telangiectases, arteriovenous malformations with recurrent epistaxis and hemorrhages, and inheritance. A wide variety of clinical manifestations in HHT have been described. In more than 90% of the patients, nosebleeds are the first predominant symptom, therefore ENT physicians often play a key role as far as diagnosis and management of the disease are concerned. In spite of recent diagnostic and therapeutic progress, a cure for this often burdening and handicapping disease is still not available. Apart from affecting the nose, arteriovenous malformations (AVMs) may also affect the skin, lungs, brain, liver and gastrointestinal tract. The two known genes that are implicated in HHT are endoglin (ENG) located on chromosome 9q33-q34 and activin-receptor-like kinase (ALK1) located on chromosome 12q13. Mutations of ENG are observed in HHT type 1 with an incidence up to 40% for pulmonary AVMs, whereas mutations of ALK1 are observed in HHT type 2 with an incidence of only 14% for pulmonary AVMs, which clinically distinguishes these two types of mutation. The emphasis of this paper is mainly on the clinical manifestation, molecular genetics and diagnosis of HHT, taking account of current literature on HHT in order to better understand the complexity of the disease. Recent therapeutic options in the treatment of HHT have been omitted from this paper as they are subject of a following paper. HHT is more common than previously thought and shows a broad range of different clinical organ manifestations that can be sources of substantial morbidity and mortality, making HHT a continuing challenge for many sub-specialties where interdisciplinary diagnostic screening is mandatory in the management of the disease.